Building the Image of Semarang City through Motocross World Championship - Mahrani Mahrani; Poppy Ruliana; Rajab Ritonga (Ikatan Sarjana Komunikasi Indonesia, 2020)
This research discusses how motocross world championship MXGP 2019 in Semarang City improved the image of the Indonesian tourism. This research also aims to see how the event has an effect on the motocross fan community in Semarang particularly to look at the development of sports tourism and future trend of sports tourism in Indonesia. This research uses qualitative approaches. Data were collected through a semi-structured interview technique to analyze motocross grand prix world championship 2019 held to improve the image of sport tourism. Key informant is Lightining Production as the organizer of the motocross grand prix world championship. The other informants are Youthstream, Semarang Mayor, Chief of the Indonesian Motorcycle Association and 10 spectators of Motocross MXGP World Championship 2019. The views of the informants were analyzed to yield findings and recommendations to develop the image of tourism in Indonesia, particularly Semarang City. The result of this research shows the Motocross Grand Prix World Championship 2019 could increase the image of sport tourism and give large contributions to the development of tourism in Semarang City.